How leadership styles affect employee motivation in the hotel industry in China - Dong, Shuchi (2022)
Employee motivation has always been an important factor in organisational development, and certainly in the hospitality industry. However, according to the survey, in Chinese hotel industry, the improvement of employee motivation is a difficult problem to overcome. Additionally, Chris Mumford, a professional recruiting management on behalf of hotels, explains that a successful leader is the key to boosting employee motivation. Thus, the purpose of this study is to investigate the relationship between leadership and employee motivation, and to measure leadership styles that are effective in enhancing employee intrinsic motivation in the hospitality industry in China. Specifically, in this study, a quantitative data collection method is adopted, that is, through the questionnaire survey of Chinese hotel employees. In addition, SPSS is applied to analyse the gathered quantitative data and make a comparison with the theories and studies analysed in the literature review. Therefore, the result of this study show that intrinsic motivation is a vital autonomous motivating factor in the hospitality industry in China. Furthermore, among the five sub-dimensions of transformational leadership model, inspirational communication and intellectual stimulation have more obvious positive effects on intrinsic motivation.